Automatic question calibration for web-based testing - Ho, Thanh Nghia. (2013)
Mathematics is an important subject can be applied to many different fields of our daily life. To improve Mathematics knowledge, the best way is through practicing and doing as many exercises as possible. The traditional approach to access a student’s ability is through the standard written tests and exams. However, these kinds of tests usually have long durations and they are catered for large group of students with different knowledge levels. Hence, it may not reflect the true ability of a student. Recently, with the rapid growth of the Internet and mobile devices, online assessment seems to be a new promising approach for self-assessment in Mathematics and also in other subjects as well. The objective of the project is to tackle the two problems faced in an online assessment system: Online Test Paper Generation and Automatic Question Calibration.